Pengaruh Ukuran Perusahaan, Struktur Aktiva, dan Pertumbuhan Penjualan Terhadap Struktur Modal: (Studi pada Perusahaan Makanan dan Minuman Periode 2019-2022) - Raisa Raisa; Cahyadi Husadha; Elia Rossa (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to analyze and test the influence of company size, asset structure and sales growth on capital structure. This research method uses a quantitative type of research. The data used in this research is secondary data in the form of company annual financial reports obtained through the official website of the Indonesia Stock Exchange. The sampling technique used was purposive sampling so that 32 companies were obtained from 84 companies listed on the Indonesia Stock Exchange (BEI) and the number of observations was 128 sample data. Data processing in this research uses Eviews 12 software. The results of this research show that company size has a significant effect on capital structure, asset structure has no significant effect on capital structure, and sales growth has a significant effect on capital structure.